Unity Sum

7 2 3 m = 1 72 a 1 t 1 h 1 ω m a t h ( a t h ) 2 = A π B C \large \displaystyle 72^3\sum _{m=1}^{72}\sum _{a\ge 1}^{ }\sum _{t\ge 1}^{ }\sum _{h\ge 1}^{ }\frac{\omega^{math}}{(ath)^2}=\frac{A\pi ^B}{C}

The equation above holds true where ω = e 2 i π / 72 \omega=e^{2i \pi/72} . Find the value of A + B + C A+B+C

Bonus : Generalise for

k s b = 1 k a 1 1 a 2 1 a n 1 w b a 1 a 2 a n ( a 1 a 2 . . . a n ) s , \large k^s\sum _{b=1}^k\sum _{a_1\ge 1}^{ }\sum _{a_2\ge 1}^{ }\cdots \sum _{a_n\ge 1}^{ }\frac{w^{ba_1a_2\cdots a_n}}{\left(a_1a_2...a_n\right)^s} \; ,

where w = e 2 i π / k w=e^{2i \pi/k} .


The answer is 7382.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Apr 2, 2016

To begin with, m = 1 72 ω j m = { 72 72 j 0 o . w . \sum_{m=1}^{72} \omega^{jm} \; = \; \left\{ \begin{array}{lll} 72 & \qquad & 72 \big| j \\ 0 & & \mathrm{o.w.} \end{array} \right. and hence the sum is S = 7 2 3 m = 1 72 a 1 b 1 c 1 ω m a b c ( a b c ) 2 = 7 2 4 a , b , c 1 72 a b c 1 ( a b c ) 2 = 7 2 2 N 1 X ( N ) N 2 \begin{array}{rcl} S & = & \displaystyle 72^3 \sum_{m=1}^{72} \sum_{a \ge 1} \sum_{b\ge 1} \sum_{c\ge 1} \frac{\omega^{mabc}}{(abc)^2} \; = \; 72^4 \sum_{{a,b,c \ge 1} \atop {72 \big| abc}} \frac{1}{(abc)^2} \\ & = & \displaystyle 72^2 \sum_{N \ge 1} \frac{X(N)}{N^2} \end{array} where X ( N ) = { ( a , b , c ) N 3 a b c = 72 N } = ( 1 σ 0 ) ( 72 N ) , X(N) \; = \; \left| \big\{ (a,b,c) \in \mathbb{N}^3 \,\big| \, abc = 72N \big\} \right| \; = \; \big(1 \star \sigma_0\big)(72N) \;, where σ 0 ( n ) \sigma_0(n) is the number of divisors of n n and \star is the Dirichlet convolution, so that X ( N ) = ( 1 1 1 ) ( 72 N ) . X(N) \; = \; (1 \star 1 \star 1)(72N) \;. Now the function 1 1 1 1 \star 1 \star 1 is multiplicative. If we let S S be the set of positive integers that are coprime to 6 6 , then ζ ( 2 ) 3 = N 1 ( 1 1 1 ) ( N ) N 2 = a , b 0 c S ( 1 1 1 ) ( 2 a 3 b c ) 2 2 a 3 2 b c 2 = ( a 0 ( 1 1 1 ) ( 2 a ) 2 2 a ) ( b 0 ( 1 1 1 ) ( 3 b ) 3 3 b ) ( c S ( 1 1 1 ) ( c ) c 2 ) = ( a 0 1 2 ( a + 1 ) ( a + 2 ) 2 2 a ) ( b 0 1 2 ( b + 1 ) ( b + 2 ) 3 3 b ) ( c S ( 1 1 1 ) ( c ) c 2 ) = ( 1 1 4 ) 3 ( 1 1 9 ) 3 ( c S ( 1 1 1 ) ( c ) c 2 ) . \begin{array}{rcl} \zeta(2)^3 & = & \displaystyle \sum_{N \ge 1} \frac{(1 \star 1 \star 1)(N)}{N^2} \; = \; \sum_{a,b \ge 0} \sum_{c \in S} \frac{(1 \star 1 \star 1)(2^a3^bc)}{2^{2a}3^{2b}c^2} \\ & = & \displaystyle\left(\sum_{a \ge 0} \frac{(1 \star 1 \star 1)(2^a)}{\displaystyle 2^{2a}}\right) \left( \sum_{b \ge 0} \frac{(1 \star 1 \star 1)(3^b)}{3^{3b}}\right) \left(\sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2}\right) \\ & = & \displaystyle \left(\sum_{a \ge 0} \frac{\frac12(a+1)(a+2)}{2^{2a}}\right) \left( \sum_{b \ge 0} \frac{\frac12(b+1)(b+2)}{3^{3b}}\right) \left(\sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2}\right) \\ & = & \displaystyle \big(1 - \tfrac14\big)^{-3} \big(1 - \tfrac19\big)^{-3} \left( \sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2}\right) \;. \end{array} Similarly S = 7 2 2 N 1 ( 1 1 1 ) ( 72 N ) N 2 = 7 2 2 a , b 0 c S ( 1 1 1 ) ( 2 a + 3 3 b + 2 c ) 2 2 a 3 2 b c 2 = 7 2 2 ( a 0 ( 1 1 1 ) ( 2 a + 3 ) 2 2 a ) ( b 0 ( 1 1 1 ) ( 3 b + 2 ) 3 2 b ) ( c S ( 1 1 1 ) ( c ) c 2 ) = 7 2 2 ( a 0 1 2 ( a + 4 ) ( a + 5 ) 2 2 a ) ( b 0 1 2 ( b + 3 ) ( b + 4 ) 3 2 b ) ( c S ( 1 1 1 ) ( c ) c 2 ) = 7 2 2 f 3 ( 1 4 ) f 2 ( 1 9 ) ( c S ( 1 1 1 ) ( c ) c 2 ) \begin{array}{rcl} \displaystyle S & = & \displaystyle 72^2 \sum_{N \ge 1} \frac{(1 \star 1 \star 1)(72N)}{N^2} \\ & = & \displaystyle 72^2\sum_{a,b \ge 0} \sum_{c \in S} \frac{(1 \star 1 \star 1)(2^{a+3}3^{b+2}c)}{2^{2a}3^{2b}c^2} \\ & = & \displaystyle 72^2 \left( \sum_{a \ge 0} \frac{(1 \star 1 \star 1)(2^{a+3})}{2^{2a}}\right)\left(\sum_{b\ge 0} \frac{(1 \star 1 \star 1)(3^{b+2})}{3^{2b}}\right) \left(\sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2}\right) \\ & = & \displaystyle 72^2 \left(\sum_{a \ge 0} \frac{\frac12(a+4)(a+5)}{2^{2a}}\right)\left(\sum_{b \ge 0} \frac{\frac12(b+3)(b+4)}{3^{2b}}\right) \left(\sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2} \right) \\ & = & \displaystyle 72^2 f_3(\tfrac14) f_2(\tfrac19) \left(\sum_{c \in S} \frac{(1 \star 1 \star 1)(c)}{c^2}\right) \end{array} where f 3 ( x ) = a 0 1 2 ( a + 4 ) ( a + 5 ) x a = ( 10 15 x + 6 x 2 ) ( 1 x ) 3 f 2 ( x ) = b 0 1 2 ( b + 3 ) ( b + 4 ) x b = ( 6 8 x + 3 x 2 ) ( 1 x ) 3 \begin{array}{rcl} f_3(x) & = & \displaystyle \sum_{a \ge 0} \tfrac12(a+4)(a+5)x^a \; = \; (10 - 15x + 6x^2)(1 - x)^{-3} \\ f_2(x) & = & \displaystyle \sum_{b \ge 0} \tfrac12(b+3)(b+4)x^b \; = \; (6 - 8x + 3x^2)(1 - x)^{-3} \end{array} and hence S = 7 2 2 ( 10 15 4 + 6 16 ) ( 6 8 9 + 3 81 ) ζ ( 2 ) 3 = 7367 9 π 6 \begin{array}{rcl} S & = & \displaystyle 72^2\big(10 - \tfrac{15}{4} + \tfrac{6}{16}\big)\big(6 - \tfrac89 + \tfrac{3}{81}\big)\zeta(2)^3 \\ & = & \displaystyle \tfrac{7367}{9}\pi^6 \end{array} making the answer 7367 + 6 + 9 = 7382 7367 + 6 + 9 = \boxed{7382} .

Here is the generalization. Assume that s > 1 s > 1 throughout.

If ω = e 2 π i k \omega = e^{\frac{2\pi i}{k}} , then ω j = 1 \omega^j = 1 if and only if k j k \big| j , and hence b = 1 k ω b j = { k k j 0 o . w . \sum_{b=1}^k \omega^{bj} \; = \; \left\{ \begin{array}{lll} k & \qquad & k \big| j \\ 0 & & \mathrm{o.w.} \end{array} \right. Thus S k = k s b = 1 k a 1 1 a 2 1 a n 1 ω b a 1 a 2 a n ( a 1 a 2 a n ) s = k s + 1 a 1 , a 2 , , a n 1 k a 1 a 2 a n 1 ( a 1 a 2 a n ) s = k N 1 { ( a 1 , a 2 , , a n ) N n a 1 a 2 a n = k N } ( a 1 a 2 a n ) s = k ( 1 , n ) ( k N ) N s \begin{array}{rcl} S_k & = & \displaystyle k^s\sum_{b =1}^k \sum_{a_1 \ge 1} \sum_{a_2 \ge 1} \cdots \sum_{a_n \ge 1} \frac{\omega^{ba_1a_2\cdots a_n}}{(a_1a_2 \cdots a_n)^s} \\ & = & \displaystyle k^{s+1}\sum_{{a_1,a_2,\ldots,a_n \ge 1} \atop {k \big| a_1a_2\cdots a_n}} \frac{1}{(a_1a_2 \cdots a_n)^s} \\ & = & \displaystyle k \sum_{N \ge 1} \frac{\big| \big\{ (a_1,a_2, \ldots, a_n) \in \mathbb{N}^n \,\big|\,a_1a_2 \cdots a_n = kN \big\} \big|}{(a_1a_2 \cdots a_n)^s} \\ & = & \displaystyle k \frac{\big(1^{\star,n}\big)(kN)}{N^s} \end{array} where 1 , n 1^{\star,n} is the n n -fold Dirichlet convolution of the constant function 1 1 with itself (so that, for instance, 1 , 2 = σ 0 1^{\star,2} = \sigma_0 is the ``number of divisors" function, and 1 , 3 1^{\star,3} is what was referred to previously as 1 1 1 1 \star 1 \star 1 ).

A simple induction shows us that ( 1 , n ) ( p a ) = ( a + n 1 a ) \big(1^{\star,n}\big)(p^a) \,=\, {a + n-1 \choose a} for any prime p p and any integers n 1 n \ge 1 and a 0 a \ge 0 , and hence a 0 ( 1 , n ) ( p a ) p a s = a 0 ( a + n 1 a ) ( p s ) a = ( 1 p s ) n \sum_{a \ge 0} \frac{\big(1^{\star,n}\big)(p^a)}{p^{as}} \; = \; \sum_{a \ge 0} \binom{a + n - 1}{a}\big(p^{-s}\big)^a \; = \; \big(1 - p^{-s}\big)^{-n} for all primes p p and all integers n 1 n \ge 1 .

Suppose that the integer k k has prime factorization k = p 1 α 1 p 2 α 2 p m α m k \,=\, p_1^{\alpha_1} p_2^{\alpha_2} \cdots p_m^{\alpha_m} for primes p 1 , p 2 , , p m p_1,p_2,\ldots,p_m and positive integers α 1 , α 2 , , α m \alpha_1,\alpha_2,\ldots,\alpha_m . Let S ( k ) S(k) be the set of positive integers which are coprime to k k . Then ζ ( s ) n = N 1 ( 1 , n ) ( N ) N s = β 1 0 β 2 0 β m 0 c S ( k ) ( 1 , n ) ( p 1 β 1 p 2 β 2 p m β m c ) p 1 β 1 s p 2 β 2 s p m β m s c s = j = 1 m ( β 0 ( 1 , n ) ( p j β ) p j β s ) × ( c S ( k ) ( 1 , n ) ( c ) c s ) = ( j = 1 m ( 1 p j s ) n ) × ( c S ( k ) ( 1 , n ) ( c ) c s ) \begin{array}{rcl} \zeta(s)^n & = & \displaystyle \sum_{N \ge 1} \frac{\big(1^{\star,n}\big)(N)}{N^s} \\ & = & \displaystyle \sum_{\beta_1\ge 0} \sum_{\beta_2 \ge 0} \cdots \sum_{\beta_m \ge 0} \sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(p_1^{\beta_1} p_2^{\beta_2} \cdots p_m^{\beta_m} c)}{p_1^{\beta_1s} p_2^{\beta_2s} \cdots p_m^{\beta_m s} c^s} \\ & = & \displaystyle \prod_{j=1}^m \left(\sum_{\beta \ge 0} \frac{\big(1^{\star,n}\big)(p_j^{\beta})}{p_j^{\beta s}}\right) \times \left(\sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(c)}{c^s}\right) \\ & = & \displaystyle \left(\prod_{j=1}^m \big(1 - p_j^{-s}\big)^{-n}\right) \times \left(\sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(c)}{c^s}\right) \end{array} We also note the identity ( 1 x ) n a 0 ( a + b + n 1 a + b ) x a + b = b ( b + n 1 b ) B x ( b , n ) x < 1 (1-x)^n\sum_{a \ge 0} {a + b + n - 1 \choose a+b}x^{a+b} \; = \; b {b+n-1 \choose b} B_x(b, n) \qquad |x| < 1 for integers b , n 1 b,n \ge 1 , where B x ( b , n ) B_x(b,n) is the incomplete Beta function. Thus S k = k N 1 ( 1 , n ) ( k N ) N s = k β 1 0 β 2 0 β m 0 c S ( k ) ( 1 , n ) ( p 1 α 1 + β 1 p 2 α 2 + β 2 p m α m + β m c ) p 1 β 1 s p 2 β 2 s p m β m s c s = k j = 1 m ( β 0 ( 1 , n ) ( p j α j + β ) p j β s ) × ( c S ( k ) ( 1 , n ) ( c ) c s ) = k j = 1 m [ β 0 ( α j + β + n 1 α j + β ) ( p j s ) β ] × ( c S ( k ) ( 1 , n ) ( c ) c s ) = k 1 + s j = 1 m [ β 0 ( α j + β + n 1 α j + β ) ( p j s ) α j + β ] × ( c S ( k ) ( 1 , n ) ( c ) c s ) = k 1 + s ζ ( s ) n j = 1 m [ ( 1 p j s ) n β 0 ( α j + β + n 1 α j + β ) ( p j s ) α j + β ] = k 1 + s ζ ( s ) n j = 1 m [ α j ( α j + n 1 α j ) B p j s ( α j , n ) ] . \begin{array}{rcl} S_k & = & \displaystyle k \sum_{N \ge 1}\frac{\big(1^{\star,n}\big)(kN)}{N^s} \\ & = & \displaystyle k \sum_{\beta_1\ge0}\sum_{\beta_2\ge0} \cdots \sum_{\beta_m \ge 0} \sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(p_1^{\alpha_1+\beta_1} p_2^{\alpha_2+\beta_2} \cdots p_m^{\alpha_m+\beta_m}c)}{p_1^{\beta_1s} p_2^{\beta_2 s} \cdots p_m^{\beta_m s} c^s} \\ & = & \displaystyle k \prod_{j=1}^m \left(\sum_{\beta \ge 0} \frac{\big(1^{\star,n}\big)(p_j^{\alpha_j+\beta})}{p_j^{\beta s}}\right) \times \left(\sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(c)}{c^s}\right) \\ & = & \displaystyle k \prod_{j=1}^m \left[\sum_{\beta \ge 0} \binom{\alpha_j + \beta + n - 1}{\alpha_j + \beta}\big(p_j^{-s}\big)^\beta\right] \times \left(\sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(c)}{c^s}\right) \\ & = & \displaystyle k^{1+s} \prod_{j=1}^m \left[\sum_{\beta \ge 0} \binom{\alpha_j + \beta + n - 1}{\alpha_j + \beta}\big(p_j^{-s}\big)^{\alpha_j+\beta}\right] \times \left(\sum_{c \in S(k)} \frac{\big(1^{\star,n}\big)(c)}{c^s}\right) \\ & = & \displaystyle k^{1+s} \zeta(s)^n \prod_{j=1}^m \left[\big(1 - p_j^{-s}\big)^n \sum_{\beta \ge 0} {\alpha_j + \beta + n - 1 \choose \alpha_j + \beta}\big(p_j^{-s}\big)^{\alpha_j+\beta}\right] \\ & = & \displaystyle k^{1+s} \zeta(s)^n \prod_{j=1}^m \left[ \alpha_j \binom{\alpha_j + n - 1}{\alpha_j} B_{p_j^{-s}}(\alpha_j,n)\right] \;. \end{array}

Mark Hennings - 5 years, 2 months ago

Log in to reply

Pi Han Goh - 5 years, 2 months ago

Hi @Mark Hennings we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.

Brilliant Mathematics Staff - 5 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...